The Influence of Internal Control and Organizational Culture on Fraud Prevention at PT Swabina Gatra - Wulandari, Budi; Syaiful, Syaiful (Indonesian Vocational Research Journal, 2024)
fraud occurs a lot in the corporate environment according to the fraud triangle theory, fraud occurs because of three audit standards, namely pressure, opportunity and opportunity. such as financial fraud, data manipulation, not complying with standard operating procedures. Therefore the authors took this research with the aim of analyzing the effect of internal control and organizational culture on fraud prevention at PT Swabina Gatra. This study aims to determine the effect between the independent variable and the dependent variable. The sample for this study consisted of 36 respondents who were employees of PT Swabina Gatra who had positions equivalent to directors, managers, unit managers, and supervisors. This study uses instrument tests such as validity and reliability tests, classical assumption tests which include normality tests, multicollinearity tests, and heterocodicity tests, followed by hypothesis testing and determination tests. The results showed that the internal control variable had an effect on fraud prevention, while the organizational culture variable had no effect on fraud prevention.